2017
DOI: 10.15171/jcvtr.2017.17
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effect of high dose allopurinol in patients with severe left ventricular systolic dysfunction

Abstract: Introduction: Allopurinol used in the treatment of gout has been shown to improve the vascular endothelial dysfunction and reduce the dysfunction of the failing heart. This study was done to evaluate the effect and safety of allopurinol in non-hyperuricemic patients with chronic severe left ventricular (LV) dysfunction. Methods: In this study, 35 consecutive cases of non-hyperuricemic patients with chronic heart failure who had severe LV systolic dysfunction (ejection fraction of less than 35%) and were on op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…The net signal from these studies was unclear, some studies claiming that UA-lowering agents improved morbidity, mortality, cardiovascular (CV) events, and hospitalizations, 10 13 while others found that UA-lowering agents do not cause any significant change in survival of patients with HF or performed even worse than placebo. 14 –20…”
Section: Introductionmentioning
confidence: 99%
“…The net signal from these studies was unclear, some studies claiming that UA-lowering agents improved morbidity, mortality, cardiovascular (CV) events, and hospitalizations, 10 13 while others found that UA-lowering agents do not cause any significant change in survival of patients with HF or performed even worse than placebo. 14 –20…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in a clinical study led on HF patients, allopurinol was able to restore M-CK activity, hence to sustain the transfer of energy from mitochondria to sarcomere (Hirsch et al, 2012 ). More recent study revealed an improvement of walk effort resistance in patients suffering from left ventricular dysfunction, even with higher administrated dose (300 mg daily for 1 week then 600 mg daily for 3 months) (Ansari-Ramandi et al, 2017 ). However, in patients undergoing percutaneous intervention, allopurinol pretreatment revealed as not effective enough to modify cardiac biomarkers, and especially the level of creatine kinase or troponin-T (Alemzadeh-Ansari et al, 2017 ; Ansari-Ramandi et al, 2017 ).…”
Section: Discussion: Therapeutic Strategiesmentioning
confidence: 99%
“…More recent study revealed an improvement of walk effort resistance in patients suffering from left ventricular dysfunction, even with higher administrated dose (300 mg daily for 1 week then 600 mg daily for 3 months) (Ansari-Ramandi et al, 2017 ). However, in patients undergoing percutaneous intervention, allopurinol pretreatment revealed as not effective enough to modify cardiac biomarkers, and especially the level of creatine kinase or troponin-T (Alemzadeh-Ansari et al, 2017 ; Ansari-Ramandi et al, 2017 ). This last work may lead to suggest the idea that relevance of such a treatment may depend on numerous parameters.…”
Section: Discussion: Therapeutic Strategiesmentioning
confidence: 99%
“…In animals, at least 11 papers reported that heart failure and ischemic heart disease were improved by the administration of allopurinol or febuxostat (DeWall et al, 1971; Arnold et al, 1980; Hopson et al, 1995; Pérez et al, 1998; Ekelund et al, 1999; Khatib et al, 2001; Ukai et al, 2001; Stull et al, 2004; Hou et al, 2006; Xu et al, 2008; Zhao et al, 2008; Yao and Seko, 2017; El-Bassossy et al, 2018). In humans, at least 20 papers, including randomized controlled trials (RCTs) and meta-analyses, reported that heart failure and ischemic heart disease were improved by the administration of allopurinol or febuxostat (Saugstad, 1996; Cappola et al, 2001; Gavin and Struthers, 2005; Pacher et al, 2006; Noman et al, 2010; Rentoukas et al, 2010; Thanassoulis et al, 2010; Kelkar et al, 2011; Gotsman et al, 2012; Hirsch et al, 2012; Agarwal and Messerli, 2013; Agarwal et al, 2013; Larsen et al, 2016; MacIsaac et al, 2016; Singh and Yu, 2016, 2017; Ansari-Ramandi et al, 2017; Foody et al, 2017; Singh et al, 2017; Bredemeier et al, 2018). Because of febuxostat’s more recent approval, most reports analyzed only allopurinol.…”
Section: Cellular Energy-charge and Atp Turnovermentioning
confidence: 99%